PEMANFAATAN MEDIA AUDIOVISUAL DALAM PEMBELAJARAN MATEMATIKA KELAS RENDAH DI MADRASAH IBTIDAIYAH - Yulina Fadilah; Silvi Andriani; Rahmat Bani; Rahmat Hasandi (LPPM STAI Muhammadiyah Probolinggo, 2023)
The development of this research was carried out to streamline the learning process and provide an understanding of the importance of using instructional media in learning activities for teachers and low-grade students at Madrasah Ibtidaiyah. Developing research aims to provide awareness of the importance of media in the learning process. This study uses a qualitative research approach by conducting a survey method. Audio-visual media is a container for conveying material or information to students and has the aim of making the learning process more effective by involving students. The results of using audio-visual media are very good and have a positive impact on students.